Test of light-lepton universality in τ decays with the Belle II experiment - The Belle II collaboration; I. Adachi; K. Adamczyk; L. Aggarwal; H. Aihara; N. Akopov; A. Aloisio; N. Anh Ky; D. M. Asner; H. Atmacan; V. Aushev; M. Aversano; et al. (Journal of High Energy Physics)
Abstract We present a measurement of the ratio R μ = B τ − → μ − ν ¯ μ ν τ / B τ − → e − ν ¯ e ν τ $$ {R}_{\mu }=\mathcal{B}\left({\tau}^{-}\to {\mu}^{-}{\overline{\nu}}_{\mu }{\nu}_{\tau}\right)/\mathcal{B}\left({\tau}^{-}\to {e}^{-}{\overline{\nu}}_e{\nu}_{\tau}\right) $$ of branching fractions B $$ \mathcal{B} $$ of the τ lepton decaying to muons or electrons using data collected with the Belle II detector at the SuperKEKB e + e − collider. The sample has an integrated luminosity of 362 ± 2 fb −1 at a centre-of-mass energy of 10.58 GeV. Using an optimised event selection, a binned maximum likelihood fit is performed using the momentum spectra of the electron and muon candidates. The result, R μ = 0.9675 ± 0.0007 ± 0.0036, where the first uncertainty is statistical and the second is systematic, is the most precise to date. It provides a stringent test of the light-lepton universality, translating to a ratio of the couplings of the muon and electron to the W boson in τ decays of 0.9974 ± 0.0019, in agreement with the standard model expectation of unity.